Membangun Aset Menjadi Berkah: Studi Edupreneurship Islami Usaha Ruko Kontrakan Ibu Sunaryati di Inderapura - Khatimah, Siti Husnul; Subiyantoro, Subiyantoro; Haryani, Arifa (Lembaga Yasin AlSys, 2025)
Micro-entrepreneurship in the property sector, particularly in rental shop-house (ruko) businesses, represents a promising strategy for fostering asset-based economic independence. However, limited research has explored female entrepreneurship practices through the lens of Islamic values, especially among MSME actors in semi-urban areas. This study aims to analyze the practice of Islamic edupreneurship in a ruko rental business managed by Ibu Sunaryati in Inderapura. A qualitative approach was employed using an exploratory case study design. Data were collected through in-depth interviews with the main entrepreneur, tenants, and community figures; participatory observation of business activities; and documentation of legal aspects such as lease contracts and building certificates. Thematic analysis was conducted using the Integrated Islamic Entrepreneurship Model (IIEM), which is grounded in three pillars: asset Islamization, entrepreneurial education values, and communal barakah (blessing). The findings reveal that this ruko rental business functions not only as a source of passive income but also embodies Islamic values such as ikhlas (sincerity), amanah (responsibility), and barakah in its daily operations. Business success is supported by a modular strategy, the application of sharia-compliant contracts (akad), and relationship management rooted in akhlaqul karimah (noble character). The study concludes that Islamic edupreneurship holds strong potential as an adaptive and sustainable model for micro-entrepreneurship. Its implications suggest that this model can be replicated by female MSME actors as a spiritually grounded approach to economic empowerment and asset-based prosperity.